What proportion of preterm births (< 34 weeks) are receiving appropriate antenatal corticosteroids and how many might benefit from a rescue dose?. (18th April 2012) - Murphy, A; King, G; Walsh, N; Mahony, R; Foley, M
Abstract : Background: Most reports on antenatal steroid use are non-specific in relation to the appropriate dose received. Purpose of study: To determine what proportion of mothers are receiving an appropriate dose of antenatal corticosteroids (betamethasone 12.5 mg 12 hourly, 2 doses, with a delivery interval of over 24 hours from completion) and to determine how many might potentially benefit form a rescue dose. Study Design and Methods: This was a consecutive observational cohort study (2008 to June 2011) of singleton preterm births (<34weeks gestation) including inuterotransfers (IUT). Findings of the study: Among 416 mothers, 286 (69%) received the appropriate dose, 315 (75%) received a complete course (29 delivered within 24 hours), 73 (17.6%) received 1 dose and 28 (6.8%) did not receive any antenatal corticosteroids. Significantly more IUTs received the appropriate dose compared with the indigenous hospital population (93/107; 87% v. 193/308; 62.6%; p <0.0001) and this difference was largely explained differences in the materno-fetal category (90%, 50/55 vs. 56%, 95/144, respectively) Of the 286 women who received the appropriate dose, 93( 33%) and 46(16%)were not delivered after 2 and 4 weeks respectively and were less than 34 weeks gestation and could be considered for rescue therapy. Conclusion: While 95 % received any steroids 69% received the appropriate dose, which was hugely influenced by the proportion of IUTs and the category of PTB; factors that should be considered when reporting antenatal steroid use and neonatal outcome. Up to one third of women might benefit from rescue therapy.